Andrés Santos Samaniego and the Roman Epigraphy of Coria, Cáceres (MS. 13.078, Biblioteca Nacional de España, Madrid) - Paredes Martín, Enrique (Gerión. Revista de Historia Antigua, 2020)
In the middle of the 18th century, the scholar Andrés Santos Samaniego, born in Salamanca, copied a series of Roman inscriptions that he found reused on the walls of Coria (Cáceres). His information constitutes the oldest news that we have about such inscriptions. Although this author’s interest was not primarily focused on the Roman epigraphy of this locality, we will point out the value of the data that the author gives us about these inscriptions, because in some cases they can be considered as the first –and certainly, the only– information telling us the formal characteristics of these pieces.